A comprehensive survey of DDoS defense solutions in SDN: Taxonomy, research challenges, and future directions. Issue 110 (November 2021) - Kaur, Sukhveer; Kumar, Krishan; Aggarwal, Naveen; Singh, Gurdeep
Highlights: Identified high quality research articles in the field of SDN-aimed DDoS attacks using a systematic literature review protocol. Revealed vulnerable points exploited by the attacker to launch DDoS attacks on SDN architecture so that root cause of the problem can be identified. Presented the taxonomy of DDoS defense solutions that classified the reviewed articles based on the attack targets, DDoS defense approaches, testing environment, and traffic generation mechanism. Performed critical analysis of existing literature based on attack targets and highlighted key research challenges in the SDN paradigm. Abstract: The recent emergence of technologies such as Network Functions Virtualization (NFV), Intent based Networking, Internet of Things (IoT), 5G, and Cloud Computing have led to the rapid growth of networks. The inflexibility and vendor-specific nature of traditional network devices are unable to fulfill the requirements of modern data centers. Software-Defined Networking (SDN) has captured data center space due to its innovative features viz. vendor neutrality, programmability, and centralized management. However, SDN is also facing various security threats due to weaknesses in its inherent architecture. This article has attempted to identify various vulnerable points in the SDN framework and has classified the SDN-aimed DDoS attacks based on their impacts. This article presents a systematic literature review on various DDoS defense mechanisms to protect the control plane, data plane, and data-control plane communication channel. In this study, a well-defined methodology is used to select the high-quality research articles of DDoS defense mechanisms in the SDN framework. Among numerous articles published in the last few years, the authors have selected 75 articles with the highest impact factor and citation. Moreover, we present the taxonomy of DDoS defense solutions that classify the reviewed articles based on the attack targets, DDoS defense approaches, testing environment, and traffic generation mechanism. Finally, we identified the research gaps and highlighted various research challenges for future research. This study is intended to serve as a ready reference for the research community to develop more efficient and reliable DDoS defense solutions in the SDN networks.